Fragmented information, divided publics: exploring the polarization between deliberative and activist orientations during Indonesian elections - Yuniar, Ananda Dwitha; Ananda, Kun Sila; Kamarudin, Syafila (Routledge, 2025)
This study examines how the management of political disagreement during elections affects the development of political information repertoires, particularly in relation to political orientation. Amid rising political polarization, particularly on social media, prevailing assumptions suggest that individuals engage with diverse perspectives. However, this research interrogates whether deliberative and partisanship groups curate political information differently or reinforce ideological divides. A cross-sectional survey was conducted with a rigorously selected sample of Indonesian voters, who demonstrated an active interest in political debates—both deliberative and partisanship. Partial Least Square was applied across two models: (1) the role of political information sources in shaping deliberative and partisanship engagement, and (2) the effects of disagreement management strategies on political discourse. The findings reveal that both deliberative and partisanship individuals actively filter, select, and curate political networks and media consumption based on ideological preferences rather than openness to diverse viewpoints. This challenges prevailing assumptions in deliberative democracy theories, suggesting that deliberative individuals may engage in political discussions selectively rather than embracing ideological diversity. The study highlights the reinforcing mechanisms of selective exposure and polarization, underscoring the role of political information repertoires in shaping electoral discourse in deeply divided societies.